2005
DOI: 10.1002/kin.20065
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the reaction of benzyl bromide with copper in hexamethylphosphoramide

Abstract: The reaction of copper with benzyl bromides in hexamethylphosphoramide has been studied. The kinetic and thermodynamic parameters of the reaction have been obtained. Hammett plots of log (k/k o ) vs the substituent constant σ gave good correlations (ρ = 0.15, S ρ = 0.02, r = 0.954). The structure of the organic group has little effect on the rate of reaction of benzyl bromide with copper. In the absence of atmospheric oxygen, the oxidative dissolution of copper occurred by the mechanism of single-electron tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…Here, with [Me 6 ‐TREN] o = 0, no polymerization occurs, although activation followed by bimolecular termination takes place. Studies into the kinetics of Cu(0) mediated activation of benzyl halides and CCl 4 , indicated that even in the absence of an N‐ligand, carbon halide bond dissociation did occur with the fastest rate being observed in DMSO solvent 35–37. Without ligand, the extent and rate disproportionation of Cu(I)Br is significantly lower than in the presence of Me 6 ‐TREN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, with [Me 6 ‐TREN] o = 0, no polymerization occurs, although activation followed by bimolecular termination takes place. Studies into the kinetics of Cu(0) mediated activation of benzyl halides and CCl 4 , indicated that even in the absence of an N‐ligand, carbon halide bond dissociation did occur with the fastest rate being observed in DMSO solvent 35–37. Without ligand, the extent and rate disproportionation of Cu(I)Br is significantly lower than in the presence of Me 6 ‐TREN.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in rate with increasing ligand concentration is consistent with Langmuir‐Hinshelwood kinetics previously proposed for Cu(0) activation of benzyl halides, if the solvent is replaced with more strongly coordinating N‐ligand (eqs 1– 3). 35–37 …”
Section: Resultsmentioning
confidence: 99%
“…The rate constant ( k ), enthalpies, and entropies of adsorption of the reactants on the surface of copper obtained here are represented in Table III in comparison with reaction of copper with benzyl bromide in DMF 1, DMAA 2, and HMPA 3.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetics‐related data of 1–3 indicate that bromine atom abstraction or single electron transfer is the most likely rate‐limiting step for the reaction of substituted benzyl bromides with copper in dipolar aprotic solvents. These data allow the authors to hypothesize a mechanism as described above 1–3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation